Identifying genetic hotspots by mapping molecular diversity of widespread trees: when commonness matters - Souto, Cintia Paola (2015)
Conservation planning requires setting priorities at the same spatial scale at which decision-making processes are undertaken considering all levels of biodiversity, but current methods for identifying biodiversity hotspots ignore its genetic component. We developed a fine-scale approach based on the definition of genetic hotspots, which have high genetic diversity and unique variants that represent their evolutionary potential and evolutionary novelties. Our hypothesis is that wideranging taxa with similar ecological tolerances, yet of phylogenetically independent lineages, have been and currently are shaped by ecological and evolutionary forces that result in geographically concordant genetic patterns. We mapped previously published genetic diversity and unique variants of biparentally inherited markers and chloroplast sequences for 9 species from 188 and 275 populations, respectively, of the 4 woody dominant families of the austral temperate forest, an area considered a biodiversity hotspot. Spatial distribution patterns of genetic polymorphisms differed among taxa according to their ecological tolerances. Eight genetic hotspots were detected and we recommend conservation actions for some in the southern Coastal Range in Chile. Existing spatially explicit genetic data from multiple populations and species can help to identify biodiversity hotspots and guide conservation actions to establish science-based protected areas that will preserve the evolutionary potential of key habitats and species.